The First Case Series of Cryopyrin-Associated Periodic Syndrome in Korea - Han, Jong Hee (Allergy Asthma Immunol Res, 2019)
Cryopyrin-associated periodic syndrome (CAPS) is a hereditary autoinflammatory syndrome caused by mutations in NLRP3 (encoding cryopyrin), which presents with fever, fatigue and arthralgia. Thus far, however there have been no reports of CAPS in Korea. Herein, we report 3 cases of CAPS for the first time in Korea. The first case, a 28-year-old man with recurrent urticaria, arthralgia and fever induced by cold, all of which were observed in his father, showed elevated erythrocyte sedimentation rate and C-reactive protein. He exhibited a p.Gly303Asp variant of the NLPR3 gene. The second case, a 2-year-old girl who had recurrent urticaria, arthritis and oral and genital ulcers, was positive for HLA B51 and a p.Glu569Lys mutation in exon 3 of the NLRP3 gene. Administration of anakinra greatly improved her symptoms. The third case, a 4-year-old boy who presented with recurrent urticaria, arthralgia, and fever, exhibited a p.Val72Met mutation in exon 1 of the NLRP3 gene. Administration of tocilizumab improved all of his symptoms. This small case series suggests that clinicians consider CAPS and conduct genetic studies when arthralgia and fever are accompanied by urticaria in Korea.